Composition Operators in Hyperbolic Bloch-Type and Fp,q,s Spaces - Marko Kotilainen; Fernando Pérez-González (Abstract and Applied Analysis)
Composition operators Cφ from Bloch-type ℬα spaces to Fp,q,s classes, from Fp,q,s to ℬα, and from Fp1,q1,0 to Fp2,q2,s2 are considered. The criteria for these operators to be bounded or compact are given. Our study also includes the corresponding hyperbolic spaces.